2020
DOI: 10.1101/2020.11.11.20230045
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impacts of the COVID-19 Pandemic on Cardiac Rehabilitation Delivery around the World

Abstract: BackgroundTo investigate impacts of COVID-19 on CR delivery around the globe, including effects on providers and patients.MethodsIn this cross-sectional study, a piloted survey was administered to CR programs globally via REDCap from April-June/2020. The 50 members of the ICCPR and personal contacts facilitated program identification.ResultsOverall, 1062(18.3% program response rate) responses were received from 70/111(63.1% country response rate) countries in the world with existent CR programs. Of these, 367(… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 33 publications
0
32
1
2
Order By: Relevance
“…In the current situation, where the main interest is to maintain public health during the COVID-19 pandemic, there were no clear recommendations on how to proceed in the rehabilitation of people diagnosed with CHD. The use of effective CR strategies based on the gold standard is problematic in current clinical practice, where CR is reduced or limited [ 15 , 25 ]. Innovative social connectivity methods during home-based CR are crucial to keeping participants motivated until the vaccine for SARS-CoV-2 is widely available.…”
Section: Discussionmentioning
confidence: 99%
“…In the current situation, where the main interest is to maintain public health during the COVID-19 pandemic, there were no clear recommendations on how to proceed in the rehabilitation of people diagnosed with CHD. The use of effective CR strategies based on the gold standard is problematic in current clinical practice, where CR is reduced or limited [ 15 , 25 ]. Innovative social connectivity methods during home-based CR are crucial to keeping participants motivated until the vaccine for SARS-CoV-2 is widely available.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to identify barriers and facilitators for patients to participate in virtual CR education sessions during the COVID-19 pandemic. As described elsewhere, 10 several CR programs adapted their services to continue supporting patients while following public health policies and regulations. Our results showed that intrapersonal, interpersonal, institutional, and environmental factors may influence whether a patient participates in virtual CR education sessions.…”
Section: Discussionmentioning
confidence: 99%
“…9 A global survey regarding the impacts of COVID-19 on CR showed that three-fourths of programs had complete or temporary cessation of services during the pandemic. 10 In addition, COVID-19 affected the structure, delivery format, and components of chronic disease care, with programs developing innovative ways to deliver the core components of CR. [11][12][13][14] Patient education is considered a core component and quality indicator of CR.…”
mentioning
confidence: 99%
“…Some applicants were struggling with the language and others had issues accessing the CRFC website within China. This is important, given the second greatest unmet need exists there after India,5 and they currently have the greatest CR growth rates globally to our knowledge 20. Initial interest has been strong.…”
Section: Discussionmentioning
confidence: 99%
“…This is important, given the second greatest unmet need exists there after India, 5 and they currently have the greatest CR growth rates globally to our knowledge. 20 Initial interest has been strong. There is a post-certification evaluation survey embedded, so we will review learner responses and modify the CRFC accordingly in the future.…”
Section: Crfc Completersmentioning
confidence: 99%